2012
DOI: 10.31018/jans.v4i1.239
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis and alleviation of salinity stress

Abstract: Several environmental factors adversely affect plant growth and development and final yield performance of a crop. Drought, salinity, nutrient imbalances (including mineral toxicities and deficiencies) and extremes of temperature are among the major environmental constraints to crop productivity worldwide. Development of crop plants with stress tolerance, however, requires, among others, knowledge of the physiological mechanisms and genetic controls of the contributing traits at different plant developmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 114 publications
2
29
0
Order By: Relevance
“…Salinity not only reduces yield of crops but also disrupts the ecological balance of the area (Aggarwal et al 2012). Several literatures have reported that arbuscular mycorrhizal (AM) fungi act as growth regulator and mitigate the harmful effects of plants exposed to salt stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity not only reduces yield of crops but also disrupts the ecological balance of the area (Aggarwal et al 2012). Several literatures have reported that arbuscular mycorrhizal (AM) fungi act as growth regulator and mitigate the harmful effects of plants exposed to salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Among the environmental stress, soil salinity globally results in the greater loss in agricultural productivity and therefore affecting the lives of humans and animals (Aggarwal et al 2012). Evelin et al (2009) reported that 50 % loss of cultivated land affected by salinity and also the photosynthesis, protein synthesis, lipid and energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, about 3.8 million ha are affected by soil salinization due to natural saline soils in Spain, Hungary, Greece, and Bulgaria, or irrigation with saline water in significant areas of Sicily and the Ebro Valley in Spain and in other smaller parts of Italy, Hungary, Greece, Portugal, France, Slovakia, and Romania [6]. Plants growing in saline soil are subjected to three distinct physiological stresses: (1) toxic effects of specific ions such as sodium and chloride, which disrupt the structure of enzymes and other macromolecules, damage cell organelles, reduce photosynthesis and respiration, inhibit protein synthesis, and induce ion deficiency [7,8]; (2) osmotic effects due to physiological drought because plants must maintain lower internal osmotic potential to prevent water from moving from the roots into the soil [9]; and (3) nutrient imbalances caused by depression in uptake and/or transport [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mycorrhizae did not increase the dry matter in the control treatment plants. Arbuscular mycorrhizal fungi promote a better absorption of nutrients, compartmentalization of toxic ions, and production of osmolytes that mitigate the effects of salinity (Aggarwal et al, 2012). Phosphorus is one of the nutrients that have its absorption increased by the presence of AMF in the roots (Saboya et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The AMF penetrate plant roots and their network of hyphae spreads in the soil, highly increasing the surface area for absorption (Silva et al, 2001;Latef & Miransari, 2014;Bonfante & Desirò, 2015). However, under saline conditions, the difficulty in obtaining water affects the germination of AMF spores and the symbiosis is not always established (Sheng et al, 2008;Aggarwal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%